THE EFFECT OF CTL MODELS AND ACTIVITY OF STUDENTS. TOWARDS LEARNING RESULTS (JURNAL ECONOMICA : Research of Economic And Economic Education, 2020)
This study aims to determine the effect of the CTL (Contextual Teaching And Learning) model (X1) and student activity (X2) on student learning outcomes (Y) class XI IPS SMAN 7 Mandau Duri 2018/2019 Academic Year. This type of research is Quasi Experimental Design. This research was conducted at SMAN 7 Mandau Duri. This study was conducted in December 2019. The population in this study was students of class XI IPS at SMA N 7 Duri who were enrolled in the 2019/2020 school year, totaling 60 people. Sampling using Simple Random Sampling technique. The instrument used for the study was a closed questionnaire with the use of the Anova two-way test. The results showed that students who were taught using the Question Students Have method had significantly higher learning outcomes compared to students taught through the Conventional Method with Sig. = 0,000, smaller than the value of α = 0.05 (Sig. <Α). It is recommended for subject teachers to use the CTL (Contextual Teaching and Learning) learning method in the learning process at SMAN 7 Mandau Duri, especially in economics.Keywords: Contextual Teaching and Learning method, Student Activity, student learning results in the subject of Economy